Increasing the communicative literacy of contact zone employees at restaurant business enterprises - E. V. Khokhlova; O. I. Belozerova (Вестник Северо-Кавказского федерального университета, 2024)
Introduction. To maintain and grow economic indicators, service organizations must be able to compete in maintaining their place in the niche of the services provided. When considering the managerial aspects of service activities in relation to subjects of the restaurant business, one should not lose sight of such a feature as communication that arises in the service process.The signiﬁcance of this phenomenon is undeniable in any service sector, however, it is in a restaurant that the role of the interaction between employee and guest increases.Goal. To identify tools for increasing the communicative competence of employees in the contact zone of restaurant business enterprises and substantiate their role in managing the impressions and satisfaction of consumers of service services, increasing the image and competitiveness of an economic entity.Materials and methods. The research was carried out on the basis of systemic and process approaches, using dialectical and inductive methods, as well as using content analysis and synthesis of scientiﬁc information in Russian.Results and discussion. The results of the study made it possible to identify key mistakes in the behavior of employees in the contact area of restaurants and formulate the main directions for improving their communication literacy and quality of service. The model for developing the communicative competence of employees developed during the study is aimed at combining the theoretical and methodological basis of human resource management in organizations with speciﬁc types of activities and stages of developing the communicative competence of service workers.Conclusion. It is concluded that one of the important factors in increasing the competitiveness of restaurant business enterprises should be the targeted and balanced use of tools to improve the level of communicative competence of contact personnel, which will create positive impressions among customers and signiﬁcantly increase their loyalty to the establishment.